GHG Mitigation Actions MRV Issues and Options - Ellis, Jane (OECD/IEA Climate Change Expert Group Papers, 2009)
The Bali Action Plan (BAP) language on "measurable, reportable and verifiable" (MRV) greenhouse gas mitigation actions and commitments for a post-2012 climate framework was introduced to apply both to developed countries' greenhouse gas (GHG) commitments and actions (paragraph 1(b)(i) of the BAP), as well as to "nationally appropriate mitigation actions by developing country Parties in the context of sustainable development, supported and enabled by technology, financing and capacity-building" (paragraph 1(b)(ii)). This paper provides an overview of current efforts to assess if GHG mitigation actions underway in different countries and regions are "measurable, reportable and verifiable".